Exiles in the City : Hannah Arendt and Edward W. Said in Counterpoint - Spanos, William V. (Book collections on Project MUSE., 2012)
"As variations on the theme of exile, the five chapters of this book constitute reflections on what is foundational and abiding in both Arendt's and Said's work. They not only document the heretofore unnoticed affiliation between the two thinkers. They also shed light on Arendt's and Said's proleptic activist explorations of the urgent "question of Palestine," especially on the fraught present situation, which bears increasing witness to the irony that the Israeli nation-state's "solution" has, from the beginning, systematically repeated the degradations the Jewish people suffered at the hands of German nationalism"--Publisher's description